Thermal annealing induced recovery of damaged surface layer for enhanced ferroelectricity in Bi-based ceramics. (21st August 2019) - Nam, Hyunwook; Kim, Sangwook; Khanal, Gopal Prasad; Fujii, Ichiro; Ueno, Shintaro; Wada, Satoshi
Abstract: The role of thermal annealing treatment in the enhancement of the piezoelectric and ferroelectric properties of 0.3BaTiO3 –0.1Bi(Mg1/2 Ti1/2 )O3 –0.6BiFeO3 (0.3BT–0.1BMT–0.6BF) lead-free piezoelectric ceramics was investigated. Mechanical stress induced by ceramic processing such as polishing and cutting could severely affect the electrical properties of 0.3BT–0.1BMT–0.6BF lead-free piezoelectric ceramics. In order to explore the impact of mechanical processing on their electrical properties, polished and cut samples were thermally annealed to remove damaged surface layers. It was found that the remanent polarization ( P r ; 27.27 μ C cm −2 ) and large-field piezoelectric coefficient ( d 33 *; 334 pm V −1 ) for the thermally annealed sample were remarkably enhanced in comparison to those of the polished sample ( P r of 17.57 μ C cm −2 and d 33 * of 271 pm V −1 ). This significant enhancement of piezoelectric and ferroelectric properties in thermally annealed ceramics, without any considerable change in grain size, suggests a major contribution of thermal annealing to the removal of damaged surface layers.